The comparative study of polymers for sliding pairs with UNMT (Universal Nano/Micro Tester) - Król, Artur; Gocman, Krzysztof (Tribologia - Finnish Journal of Tribology, 2017)
In the article the results of comparative research of eight types of polymers, used in sliding pairs, are presented. For the selected polymers mechanical properties and then also their tribological characteristics were examined with UNMT (UNMT - Universal Nano/Micro Tester) to select the best material. Friction coefficient and wear measurements were performed with reciprocating ball-on-disk pair of UNMT under dry lubrication conditions. The usefulness of UNMT was confirmed as a quick and precise method. Presented results showed also that the best antifriction and anti-wear properties were observed for polymer with small hardness and elasticity module.